2022
DOI: 10.1186/s12905-022-01808-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of healthcare professionals working in a training and research hospital on early diagnosis of cervical cancer (a Somalia example): cross-sectional study

Abstract: Background Despite the early diagnosis and treatment of cervical cancer, it is still a significant public health problem in Somalia. This study was conducted to evaluate the knowledge and attitudes of healthcare professionals towards the early diagnosis of cervical cancer. Methods This study was conducted in Mogadishu, the capital of Somalia, between December 2020 and February 2021. The cross-sectional study consisted of a total of 280 healthcare p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…The low coverage of formal training activities among health professionals could have led to low screening among women in this study. A study from Somalia showed that only 22.1% of the participants had cervical cancer training during their pre-service education and 16.8% in-service training after graduation [ 46 ]. In contrast, the study from Turkey indicated that nearly 75% of the health professionals had training as part of their pre-service education, and almost 67% had in-service training on cervical cancer after their graduation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low coverage of formal training activities among health professionals could have led to low screening among women in this study. A study from Somalia showed that only 22.1% of the participants had cervical cancer training during their pre-service education and 16.8% in-service training after graduation [ 46 ]. In contrast, the study from Turkey indicated that nearly 75% of the health professionals had training as part of their pre-service education, and almost 67% had in-service training on cervical cancer after their graduation [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios concuerdan con nuestros resultados y describen que el conocimiento sobre signos y síntomas y factores de riesgo de cáncer de cuello uterino, fue adecuado entre los profesionales de la salud (28)(29)(30). Sin embargo, otros estudios encontraron que el personal de salud tenían escaso conocimiento del cáncer de cuello uterino como enfermedad (31,32) y la formación de los profesionales sanitarios que trabajan en el sector salud para el diagnóstico precoz del cáncer de cuello uterino no son suficientes (33). Estas diferencias pueden deberse a las políticas de Fuente: encuesta aplicada, *= Prueba U de Mann-Whitney salud, presupuesto destinado las capacitaciones y motivación por seguir aprendiendo por parte del personal de salud.…”
Section: Discussionunclassified